Bangladesh under Mujib, Zia and Ershad : dilemma of a new nation - Chakravarti, S. R. (New Delhi : Har-Anand Publications, 1995)
Political developments in Bangladesh; covers the period 1972-1990.
Includes bibliographical references (p. [297]-299) and index.
Rasal
Keywords: Mujibur Rahman, -- Sheikh, -- 1920-1975.; Rahman, Ziaur, -- 1936-1981.; Ershad, Hussain Muhammad, -- 1930-; Bangladesh -- Politics and government -- 1971-